Li+ and Sm3+ co-doped AgNbO3-based antiferroelectric ceramics for high-power energy storage. Issue 22 (15th November 2022) - Tian, Ye; Song, Panpan; Gu, Rui; Xu, Yonghao; Jin, Li; Wang, Tong; Wei, Xiaoyong; Ge, Wanyin
Abstract: Ag1-x-3y Lix Smy NbO3 (x≤0.05, y≤0.05) (ALSN) antiferroelectric ceramics were successfully prepared via conventional solid-state reaction and sinter routes in oxygen atmosphere for improving the energy storage characteristic of pure AgNbO3 . The results indicate that all of the studied compositions display a pure orthorhombic antiferroelectric (AFE) perovskite structure, while their key parameters of electric-field-induced antiferroelectric-ferroelectric transition can be affected by Li + or/and Sm 3+ doping contents. The Sm 3+ doping can enhance the stability of antiferroelectric state, giving rise to higher antiferroelectric-ferroelectric transition electric-field (EF and EB ), while Li + doping can reduce EF and EB for Sm 3+ doped AgNbO3 with low Sm 3+ content (y≤0.03). When co-doping the same amounts of Li + and Sm 3+ at x=y≤0.03, both EF and EB almost remain unchanged. At x=y=0.05, the diffuse phase transition (DPT) behavior of antiferroelectric-paraelectric (AFE-PE) phase transition occurred, resulting in a "slim-like" double-polarization hysteresis with significantly enhanced EF . Due to these features, both Wrec and η are improved compared with pure AgNbO3 . The Wrec and η with composition at x=y=0.05 is 2.33 J/cm 3 and 58% under applying electric field of 240 kV/cm, respectively. The results suggest that building DPT behavior of AFE-PE phase transition could be an alternative strategy to improve the energy storage characteristic of AgNbO3 .